The Correlations Between Clinical Characteristics and Inflammation Markers with Chest X-rays in COVID-19 Patients at Ulin Hospital - Muhammad Nor; Ira Nurrasyidah; Mashuri Mashuri (Jurnal Respirologi Indonesia, 2023)
Background: Chest x-ray is one of the parameters used to estimate the severity and prognosis of COVID-19. Arterial oxygen saturation (SaO2), partial pressure of arterial oxygen (PaO2), and respiratory index (PaO/FiO2) can also predict the disease severity. Other parameters, like inflammation markers, have also been used as predictors for prognosis. Based on those considerations, this study aimed to examine their connection and find their correlation.Methods: This was an analytic observational retrospective study. The samples were moderate-critical COVID-19 patients in Ulin General Hospital Banjarmasin from July to December 2021 who met the inclusion and exclusion criteria. Statistical tests were used to see the relationship between clinical characteristics and inflammation markers with chest X-rays using various scoring systems (Brixia, sRALE, and modified Soetomo score).Results: The total number of subjects was 67. The data analysis found that the severity of the disease had a significant relationship with the severity of the chest x-ray (P<0.001). The PF ratio also had a significant negative correlation (P<0.001) with the severity of the chest x-ray. For inflammation markers, NLR, CRP, and LDH significantly correlated with a chest x-ray. The patient's outcome was also associated with a chest X-ray (P<0.015).Conclusion: There were significant correlations between clinical characteristics and inflammation markers on the chest X-ray severity, and sRALE was a better scoring system to assess chest X-ray severity than other scoring systems.